COGNITIVE LOAD AND COMPENSATION STRATEGIES OF BIPA LEVEL 1 LEARNERS IN TEXT BASED WRITING (Lectio: Journal of Language and Language Teaching, 2026)
This study examines the cognitive load and compensation strategies used by BIPA Level 1 learners in producing text-based writing, focusing on how cognitive constraints shape phonological, lexical, phrasal, and syntactic errors. The purpose of this research is to analyze the intrinsic, extraneous, and germane cognitive loads reflected in students’ written errors and to identify the compensation strategies employed to overcome linguistic limitations. This research  analyzed based on cognitive load theory (Sweller, 1994) and compensation strategies (Tarone, 1983 ) and adopts a qualitative descriptive method involving nine BIPA Level 1 learners from Japan, Sweden, and Armenia. The data consist of descriptive texts (“Myself”) and procedural texts (“How to Make Favorite Foods”), collected through documentation and analyzed using the interactive model of Miles, Huberman, and Saldana (2014), which includes data reduction, data display, and conclusion drawing. The findings show that the highest cognitive load appears at the phoneme–orthography level, where learners struggle to map Indonesian phonological input into correct graphemic output, resulting in frequent phoneme substitutions, omissions, or distortions. Lexical and syntactic errors further confirm intrinsic load arising from complex forms, unfamiliar structures, and L1 interference. Extraneous load emerges from task complexity, incomplete understanding of Indonesian conventions, and performance pressure during writing. Meanwhile, germane load is visible in productive errors where learners attempt to build new linguistic schemas, such as approximating unfamiliar phonological forms or constructing new noun phrases. Three dominant compensation strategies were identified: approximation, literal translation, and word coinage, indicating learners’ efforts to maintain communicative flow despite limited proficiency.
Keywords: BIPA learners; cognitive load; compensation strategies; psycholinguistic; writing errors